Estimation of the Shoulder Joint Angle using Brainwaves - Minoru Sasaki; Takaaki Iida; Joseph Muguro; Waweru Njeri; Pringgo Widyo Laksono; Muhammad Syaiful Amri bin Suhaimi; Muhammad Ilhamdi Rusydi (Andalas Journal of Electrical and Electronic Engineering Technology, 2021)
This paper presents the angle of the shoulder joint as basic research for developing a machine interface using EEG. The raw EEG voltage signals and power density spectrum of the voltage value were used as the learning feature. Hebbian learning was used on a multilayer perceptron network for pattern classification for the estimation of joint angles 0o, 90o and 180o of the shoulder joint. Experimental results showed that it was possible to correctly classify up to 63.3% of motion using voltage values of the raw EEG signal with the neural network. Further, with selected electrodes and power density spectrum features, accuracy rose to 93.3% with more stable motion estimation.